Dictators without borders power and money in Central Asia - Cooley, Alexander 1972-; Heathershaw, John (Yale University Press, 2017)
"A penetrating look into the unrecognized and unregulated links between autocratic regimes in Central Asia and centers of power and wealth throughout the West. Weak, corrupt, and politically unstable, the former Soviet republics of Kazakhstan, Kyrgyzstan, Tajikistan, and Uzbekistan are dismissed as isolated and irrelevant to the outside world. But are they? This hard-hitting book argues that Central Asia is in reality a globalization leader with extensive involvement in economics, politics and security dynamics beyond its borders. Yet Central Asia's international activities are mostly hidden from view, with disturbing implications for world security. Based on years of research and involvement in the region, Alexander Cooley and John Heathershaw reveal how business networks, elite bank accounts, overseas courts, third-party brokers, and Western lawyers connect Central Asia's supposedly isolated leaders with global power centers. The authors also uncover widespread Western participation in money laundering, bribery, foreign lobbying by autocratic governments, and the exploiting of legal loopholes within Central Asia. Riveting and important, this book exposes the global connections of a troubled region that must no longer be ignored"-- Provided by publisher